Elevated CO2 alleviates negative impacts of high temperature and salinity on phytohormones, photosynthesis, and redox reactions in leaves of Caragana korshinskii kom - Yan, Hui (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 Elsevier Masson SAS. All rights reserved.